2001
DOI: 10.1677/erc.0.0080175
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of epidermal growth factor receptor in endocrine-resistant, oestrogen receptor-positive breast cancer.

Abstract: There is an increasing body of evidence demonstrating that growth factor networks are highly interactive with oestrogen receptor (ER) signalling in the control of breast cancer growth. As such, tumour responses to anti-hormones are likely to be a composite of the ER and growth factor inhibitory activity of these agents. The current article examines the modulation of growth factor networks during endocrine response, and presents in vitro and clinical evidence that epidermal growth factor receptor signalling, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 55 publications
1
74
0
3
Order By: Relevance
“…Therefore increased ERK activity could potentially contribute to resistance to endocrine therapy. Indeed, ERK1/2 expression and activity are increased in several breast cancer cell-line models of endocrine resistance (Coutts & Murphy 1998, Shim et al 2000, and increased ERK 1/2 activity (assessed by phosphorylated MAPK immunostaining) correlates with shorter duration of response to endocrine therapy in clinical breast cancer (Gee et al 2001).…”
Section: Peptide Growth Factor Signalling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore increased ERK activity could potentially contribute to resistance to endocrine therapy. Indeed, ERK1/2 expression and activity are increased in several breast cancer cell-line models of endocrine resistance (Coutts & Murphy 1998, Shim et al 2000, and increased ERK 1/2 activity (assessed by phosphorylated MAPK immunostaining) correlates with shorter duration of response to endocrine therapy in clinical breast cancer (Gee et al 2001).…”
Section: Peptide Growth Factor Signalling Pathwaymentioning
confidence: 99%
“…Continuous culture of MCF7 cells with either tamoxifen or the pure anti-oestrogen Fulvestrant has been shown to generate sublines which can tolerate the presence of these agents, and grow at rates equivalent to their parental lines (McClelland et al 2001, Knowlden et al 2003. Under these circumstances of anti-oestrogen resistance, parallel increases in EGFR and HER2 protein have been observed.…”
Section: Peptide Growth Factor Signalling Pathwaymentioning
confidence: 99%
“…NSCLCs in smokers and nonsmokers have different molecular signatures; NSCLC cells in smokers harbor mutations mainly in Ras and p53 genes while epidermal growth factor receptor (EGFR) mutations are less prevalent (60,64). On the other hand, NSCLC cells in nonsmokers show more widespread mutations in the kinase domain of EGFR encoded by exons 18 to 24 (38) and show high expression of p27 and Akt1 (59,69). Interestingly, the EGFR gene is amplified or overexpressed in latestage cancers in both smokers and nonsmokers, indicating that EGFR activity contributes to the growth and progression of NSCLC (54,58,60).…”
mentioning
confidence: 99%
“…Interestingly, the EGFR gene is amplified or overexpressed in latestage cancers in both smokers and nonsmokers, indicating that EGFR activity contributes to the growth and progression of NSCLC (54,58,60). Indeed, EGFR overexpression is observed in 62% of NSCLC cases and is correlated with poor prognosis (21,38,54). Studies in recent years have also shown polymorphisms in nAChR genes that correlate with NSCLC in smokers (25,37,51).…”
mentioning
confidence: 99%
“…Taken together, these data suggest a role for ErbB-2 in the survival and eventual proliferation of ER + breast cancers under low estrogen conditions. A role for EGFR (also designated ErbB-1 or HER-1) in endocrine therapy resistance has also been established in preclinical and clinical studies [16,17]. Multiple preclinical experiments have demonstrated that inhibition of ErbB-1 and/or ErbB-2 with either trastuzumab (Herceptin ® ; Genentech, Inc.; South San Francisco, CA) or a selective TK inhibitor can reverse tamoxifen resistance [18][19][20][21].…”
Section: Preclinical Data On Er and Erbb-2 Crosstalkmentioning
confidence: 99%